2019
DOI: 10.11648/j.ijepp.20190706.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Indiscriminate Charcoal Production on Nigeria Forest Estate

Abstract: Half of the world's population, and up to 95 percent in poor countries, rely on solid fuel including biomass fuel and charcoal to meet their energy needs. Fuel wood and charcoal are by far the most heavily consumed energy sources in Nigeria, rural dwellers who are the custodians of forests resources depend solely on it for livelihood and increase in demand for charcoal. Nigeria ranked the highest producer of charcoal in Africa and second in the world and the production trend of charcoal in Nigeria has over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…There is a steady increase in annual production of charcoal in Nigeria yet Nigeria is not among the world's leading nations in the exporting of charcoal meaning that the nation consumes almost all that it produces. Indonesia, China and Poland led in exportation with 21.8%, 10.6% and 8.8% respectively; Nigeria is the 25th exporting nation with only 0.9% (James et al, 2019). In Nigeria, there is no controlled supply of charcoal in urban areas, and this contributes to deforestation as an increase in population in these areas results to an increase in demand for charcoal.…”
Section: Charcoal Production and Consumption In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…There is a steady increase in annual production of charcoal in Nigeria yet Nigeria is not among the world's leading nations in the exporting of charcoal meaning that the nation consumes almost all that it produces. Indonesia, China and Poland led in exportation with 21.8%, 10.6% and 8.8% respectively; Nigeria is the 25th exporting nation with only 0.9% (James et al, 2019). In Nigeria, there is no controlled supply of charcoal in urban areas, and this contributes to deforestation as an increase in population in these areas results to an increase in demand for charcoal.…”
Section: Charcoal Production and Consumption In Nigeriamentioning
confidence: 99%
“…3(2) 9-17, 2024 due to the cost of transporting charcoal from the rural areas where it is produced to the urban areas where it is widely consumed there has been a steady increase in its price and this have inhibited the growth of small-scale traders who use wood, such as fish sellers, and has also affected household budgets. Furthermore, the use of wood presently surpasses the re-growth of forests and reforestation efforts have been very poor (James et al, 2019) The Choice of Charcoal among Nigerians As reported, charcoal consumption is higher among individual and families that has low income with charcoal and fuel wood accounting for three-quarters of their total household energy expenditure (Kambewa, 2007). In weight, charcoal might be heavy or quite light depending on the weight of the dry wood of the various species used in its production.…”
Section: Charcoal Production and Consumption In Nigeriamentioning
confidence: 99%
“…These fuels are often obtained from the local community in rural areas and purchased in urban markets [13,14]. Nigerian villagers, who are the guardians of the forest's resources, rely primarily on firewood and charcoal for their livelihood, making these the country's most widely used energy sources (Figure 1) [15]. Figure 2 displays the population consuming solid fuels by region according to the World Health Organization.…”
Section: Sources Of Domestic Solid Fuels In Nigeriamentioning
confidence: 99%
“…These fuels are often obtained from the local community in rural areas and purchased in urban markets [13,14]. Nigerian villagers, who are the guardians of the forest's resources, rely primarily on firewood and charcoal for their livelihood, making these the country's most widely used energy sources (Figure 1) [15]. Figure 2 In Nigeria's rural areas, farmers who raise livestock can use a digester to turn ag cultural waste and manure into biogas, which can be used for both heating and lighti The country's yearly production of biogas is estimated at 542.5 million tons [19].…”
Section: Sources Of Domestic Solid Fuels In Nigeriamentioning
confidence: 99%
“…It was estimated that wood fuels (firewood and charcoal) account for 50 -90 % of the fuel used in developing countries [FAO, 2010;Zulu and Rihardson, 2012]. Similarly, [Rotowa et al, 2019] asserted that fuelwood and charcoal are by far the most heavily consumed energy sources in Nigeria. One great concern however is that charcoal unlike firewood is often produced from forest resources [Giraid, 2011], by means of uncontrolled and indiscriminate felling of both mature and nearly-mature trees [Subhoji, 2018].…”
Section: Introductionmentioning
confidence: 99%